Character Education Analysis of Empathy, Creativity, and Independence in The Film Totto-Chan : A Semiotic Study - Azzahra, Siti Difa Dilfayanti; Masykuroh, Khusniyati (Jurnal Paedagogy, 2025)
This study aims to explore the character formation process conducted by educators and parents in developing empathy, creativity, and independence values in Totto-chan through semiotic analysis of signs in the film. This study employs a descriptive qualitative approach with Ferdinand de Saussure’s semiotic analysis to examine signs and their meanings in the film. Data collection was conducted through comprehensive documentation of the film, focusing on dialogue, scenes, character expressions, and visual contexts. The findings of this research indicate that character formation occurs through a holistic educational approach implemented by educators and parents. Empathy character is developed through an atmosphere of acceptance and appreciation of differences, creativity is stimulated through an inspiring environment, and independence is fostered through providing trust and responsibility. The research concludes that character formation is most effective when values are not only taught explicitly but also modeled and integrated into daily practices through meaningful experiences provided to children. The contribution to character education in schools is providing a holistic education model that can be adapted into curricula, offering practical guidance for educators in creating learning atmospheres that support character formation through behavioral modeling and meaningful experiences.